Development of Web-Based Thematic Teaching Materials Using Weebly on Theme 8 Sub-theme 1 Class IV SDN 065000 Medan Marelan - Zidni Ulfi Hasanah; Erlinda Simanungkalit; Masta Marselina Sembiring; Dila Handayani (STKIP Rokania Pasir Pangaraian, 2023)
This research was conducted with the aim of knowing the feasibility and effectiveness of using Weebly-based web teaching materials on theme 8 sub-themes 1 class IV SDN 065000 Medan Marelan. This research is about research and development, which refers to the ADDIE research and development model. The results of this research and development show that web-based teaching materials using Weebly that have been developed obtain a percentage eligibility from media experts of 75% and are declared